Evaluation of the Library Management Practices of Universities in Southwest Nigeria - Ajayi, Stephen A.; Williams, Olusola Y.; Shorunke, Oludare A.; Akinola, Ayodele O. (MiddleBelt Journal of Library and Information Science, 2020)
This study evaluated library management practices of some Nigerian universities. The survey method was used to carry out this research. The population for the study comprised of heads of division, section, unit as well as faculty librarians in eight university libraries in southwest Nigeria. The sampling method adopted for the purpose of this study is simple random sampling technique. The sample size for the study is (80). Eighty questionnaires were administered and 61 was duly filled and returned and found valid for analysis, thereby, giving a response rate of 76.3%. The data was analysed using statistical Package for Social Sciences (SPSS) software version 10. The findings revealed that various management practices were in place in both the public and private university libraries just like in other organisations. Recommendations were made to improve the library management practices.